Anterograde Amnesia - Serap Erdogan (Psikiyatride Güncel Yaklaşımlar, 2010)
Memory can be divided into two categories (i.e. short term memory and long term memory) according to time span. Information at our long term memory that can be remembered with conscious effort are placed in declarative memory. Information that can not be remembered conciously are placed in nondeclarative memory. The definition of anterograde amnesia is inability to generate new memories after the event causing amnesia. Episodic and semantic memories are usually unaffected among patients’ who had such amnesia. Anterograde amnesia could mostly result from head trauma but in some cases the cause could be serebrovascular events, Wernicke-Korsakoff Syndrome, santral nervous system enfections, anoxia or various substances. Medial temporal lobe and medial diencephalon are two brain regions mainly related with this condition. Medial temporal lobe is consisted of hippocampus, amygdala, parahippocampal cortex, perirhinal cortex and entorhinal cortex. Hypothalamus, thalamus, mamillary bodies and several thalamic nucleases compose medial diencephalon. Fornix and rarely serebellum damage may also play role in the development of anterograde amnesia. After the famous H.M case, who had anterograde amnesia after an epileptic surgery operation, hippocampus has been placed in the focus of memory researches. In the literature there are several reports evaluating brain tissues of amnesic patients at postmortem stage. Postmortem histological evaluations consistently revealed hippocampal neuronal loss among these patients’ brain tissues. Benzodiazepines usually cause short term anterograde amnesia. Benzodiazepine receptors are allosteric modulatory sites on gamma-aminobutyric acid-A (GABA-A) receptors. GABA-A receptors composed of five subunits and anterograde amnesia emerges by means of alfa 1 subunit. Anterograde amnesia has been suggested to occur by the blocking of long term potentiation in hippocampus and piriform cortex. For the treatment of the anterograde amnesia, pharmacological methods usually do not work because of the neuronal loss. In order to make use of the nondeclarative memory in the treatment process, patients are educated to define their daily routines and after several training steps they get used to profit from their procedural memory. The role of social and emotional support is also very important.